Transient lymphocyte count decrease correlates with oncolytic adenovirus efficacy in humans: mechanistic and biomarker findings from TUNIMO phase I trial - Tuomo Alanko; Akseli Hemminki; Víctor Cervera-Carrascón; Riikka Havunen; Kristian Taipale; Dafne C A Quixabeira; Jorma Sormunen; Katriina Peltola; Suvi Sorsa; Santeri A Pakola; Elise Jirovec; Lyna Haybout; et al. (Journal for ImmunoTherapy of Cancer)
Background Oncolytic viruses (OVs) are promising immunotherapeutics to treat immunologically cold tumors. However, research on the mechanism of action of OVs in humans and clinically relevant biomarkers is still sparse. To induce strong T-cell responses against solid tumors, TILT-123 (Ad5/3-E2F-d24-hTNFa-IRES-hIL2, igrelimogene litadenorepvec) was developed. TILT-123 encodes two transgenes: tumor necrosis alpha (TNFa) and interleukin-2 (IL-2). TUNIMO (NCT04695327) was a phase I clinical trial using TILT-123 in patients with advanced solid tumors aiming to assess the safety, efficacy, and immunological effects of TILT-123. Research presented in this study evaluated the immunological effects of TILT-123 in the TUNIMO trial by using biological samples collected from the patients during the study, with an objective to leverage the findings to develop possible biomarkers of response and gain insights into possible synergistic combination treatments.Methods 20 patients with advanced solid tumors were treated with TILT-123. Response to therapy was assessed with contrast-enhanced CT and fluorodeoxyglucose positron emission tomography, along with overall survival (OS) calculation. Biological samples from patients were collected in the form of blood and tumor biopsies. Collected samples were analyzed with immunohistochemistry, transcriptomics, proteomics, and flow cytometry.Results TILT-123 induced cyclical decreases in blood lymphocyte count, and more substantial blood lymphocyte count correlated with better radiographical response and longer OS. Lymphocyte count findings were confirmed with external control dataset of 96 patients. More substantial lymphocyte count change was linked to stronger immune activation in plasma proteome after intravenous TILT-123 and the presence of TILT-123 mRNA in tumors. Regarding other assays. tumor biopsies profiled showed increased amounts of CD8+ T cells, CD4+ T cells and NK cells after intravenous TILT-123, but not after intratumoral TILT-123. Transcriptional differences were seen in tumors after intravenous therapy and intratumoral therapy, with patients benefitting therapy showing stronger downregulation of immune activation at all time points.Conclusions TILT-123 therapy induced accumulation of effector lymphocytes in tumors. Peripheral lymphocyte count decrease is a promising biomarker for assessing oncolytic adenovirus therapy response.